EL PRINCIPIO DE CONTINUIDAD EN LA PRESTACIÓN DE SERVICIOS PÚBLICOS DE TELECOMUNICACIONES - Gonzáles Prada, Carlos (2019)
This article develops the main characteristics and scope of the principle of continuity inthe provision of public telecommunications services, in order to determine whether saidprinciple should or not be understood literally as the requirement of an uninterruptedservice or if, otherwise, its enforcement may admit interruptions under certain parametersof tolerance. For this purpose, first we will review the notes that define the notionof public services, and in particular the obligation to guarantee its provision in a continuousmanner. Subsequently, we will analyze how the aforementioned principle materializesin the telecommunications sector. Lastly, we will evaluate the content of article44 of the Consolidated Text of the Conditions of Use of Public TelecommunicationsServices, in order to obtain a valid and reasonable interpretation for the sector.